2016
DOI: 10.1080/01616412.2015.1114290
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with potassium channel blockers of 4-aminopyridine and tetraethylammonium attenuates behavioural symptoms of Parkinsonism induced by intrastriatal injection of 6-hydroxydopamine; the role of lipid peroxidation

Abstract: Since severity of behavioural symptoms of 6-OHDA-induced Parkinsonism is correlated to the degree of nigral dopaminergic cell death, we suggest that antiparkinsonism effect of TEA and 4-AP was mediated by their neuroprotective effect. Because, both Parkinsonism in rat and PD in human, the main pathophysiological hallmark, is neurodegeneration of dopaminergic neurons in substantia nigra, we suggest doing clinical trials for evaluation of effectiveness of 4-AP and TEA in slowing down of PD progress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…On the other hand, genistein significantly raised the blood pressure in animals pre-treated with methylene blue (a monoamine oxidase and cGMP inhibitor), Tetraethylammonium (a potassium channel blocker) and Nifedipine (a calcium channel inhibitor). Although Tetraethylammonium, methylene blue and nifedipine are known blood pressure lowering drugs that produce a reduction in blood pressure via blockade of K + , cGMP induced pressure natriuresis and calcium channels respectively [11,13,14], intravenous genistein administration attenuated these blood pressure lowering effects of the drugs. Richardson et al, (2016) [23] reported that methylene blue had no effect on relaxation induced by genistein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, genistein significantly raised the blood pressure in animals pre-treated with methylene blue (a monoamine oxidase and cGMP inhibitor), Tetraethylammonium (a potassium channel blocker) and Nifedipine (a calcium channel inhibitor). Although Tetraethylammonium, methylene blue and nifedipine are known blood pressure lowering drugs that produce a reduction in blood pressure via blockade of K + , cGMP induced pressure natriuresis and calcium channels respectively [11,13,14], intravenous genistein administration attenuated these blood pressure lowering effects of the drugs. Richardson et al, (2016) [23] reported that methylene blue had no effect on relaxation induced by genistein.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure was repeated for each of the drugs in the different groups. The drugs administered include Indomethacin, a non-steroidal anti-inflammatory and a cyclooxygenase (COX-2) enzyme inhibitor (5 mg/kg subcutaneously), methylene blue, an inhibitor of nitric oxide synthase and guanylate cyclase (7.5 mg/kg, by infusion), nifedipine,a calcium channel blocker (0.75 mg/kg intravenously), and tetraethylammonium a voltage-gated K + channels blocker (60 mg/kg intravenously) [11][12][13][14]. Genistein was administered in graded doses of 0.008, 0.016, 0.032, 0.064, 0.128, and 0.256 mg/kg body weight intravenously [10], after the administration of the drugs to determine the effect and possible mechanism of actions of genistein on the blood pressure.…”
Section: Preparation and Administration Of Genistein And Different Drugsmentioning
confidence: 99%
“…1,1,3,3-tetra methoxy propane was used as standard. It should also be noted that MDA reacts with TBA to produce a pink-colored solution that has a maximum absorbance at 532 nm [22].…”
Section: Methodsmentioning
confidence: 99%
“…Total Anti-oxidant Capacity (TAC) in seminal plasma was determined according to Ferric reducing Anti-oxidant Power (FRAP) assay using small modifications [19]. Briefly, ferric tripyridyltriazine (Fe 3+ -TPTZ) complex was reduced to ferrous form (Fe 2+ -TPTZ) by the anti-oxidants in the sample at acidic pH [20,21].…”
Section: Anti-oxidant Activitymentioning
confidence: 99%